Central Counterparties : Addressing their Too Important to Fail Nature - Wendt, Froukelien (IMF Working Papers; Working Paper ;, 2015)
Central counterparties (CCPs) can offer significant benefits to a market. However, CCPs are also highly interconnected with financial institutions and markets and therefore too important to fail. The increased volumes cleared through CCPs and their increasing global scope, in particular in the OTC derivatives market, make it even more important that systemic risks related to CCPs are managed. This paper argues that the current set of international policy measures does partly address these risks, but that alternative policy measures are needed to reduce remaining systemic risks. For example, the paper recommends network analysis to be conducted by CCPs and authorities to gauge potential losses and suggests a common international approach to central bank services to help reduce the dependency of CCPs on services provided by commercial banks.